Adsorption of Expanded Pyridinium Molecules at the Electrified Interface and Its Effect on the Electron-Transfer Process - Lachmanová, Štěpánka Nováková; Dupeyre, Grégory; Lainé, Philippe P; Hromadová, Magdaléna (Langmuir, 2018)
Adsorption properties of a series of redox-active expanded pyridinium molecules were studied at an electrified interface by cyclic and alternating current voltammetry methods. It was shown that the adsorbed state can sufficiently block N-pyramidalization of the pyridinium redox center of 2',6'-diphenyl-[4,1':4',4''-terpyridin]-1'-ium tetrafluoroborate (2), leading to a change of the mechanism from a single two-electron-transfer process to stepwise transfer of two electrons. Chemically locked molecules 1, 9-(pyridin-4-yl)benzo[ c]benzo[1,2]quinolizino[3,4,5,6- ija][1,6]naphthyridin-15-ium tetrafluoroborate (ring fusion), and 3, 3,5-dimethyl-2',6'-diphenyl-[4,1':4',4''-terpyridin]-1'-ium tetrafluoroborate (steric hindrance) do not enable N-pyramidalization of the redox center upon electron transfer (ET) and serve as references. It was shown that 1 follows Langmuir-type adsorption around a potential of zero charge and that 1-3 form a close-packed film with some repulsive interactions between individual molecules at potentials where ET takes place. It has been suggested that all three molecules lie flat on the electrode surface, with the lowest free energy of adsorption found for 2. Maximum surface concentration Γ* equal to (1.4 ± 0.1) × 10-10 mol·cm-2 was found for 1, (1.5 ± 0.1) × 10-10 mol·cm-2 for 2, and (1.6 ± 0.1) × 10-10 mol·cm-2 for 3. These findings will help to clarify the role of molecular contacts with conducting substrate in the single-molecule electron-transport measurements of 1-3 during the metal-molecule-metal junction formation process.